Churchill's hellraisers : the secret mission to storm a forbidden Nazi fortress - Lewis, Damien (Citadel Press, 2020)
An impossible mission in wartime Italy: the next explosive bestseller from Damien Lewis.In the hard-fought winter of 1944 the Allied advanced northwards through Italy, but stalled on the fearsome mountainous defences of the Gothic Line. Two men were parachuted in, in an effort to break the deadlock. Their mission: to penetrate deep into enemy territory and lay waste to the Germans' impregnable headquarters.At the eleventh hour mission commanders radioed for David 'The Mad Piper' Kilpatrick to be flown in, resplendent in his tartan kilt. They wanted this fearless war hero to lead the assault, piping Highland Laddie as he went - so leaving an indelible British signature to deter Nazi reprisals.As the column of raiders formed up, there was shocking news. High command radioed through an order to stand down, having assessed the chances of success at little more than zero. But in defiance of orders, and come hell or high-water, they were going in.Damien Lewis's new bestseller tells the incredible story.